Use of chlorhexidine chip after scaling and root planning on periodontal disease: A systematic review and meta-analysis - Cleber Davi Del Rei Daltro Rosa; Jéssica Marcela de Luna Gomes; Sandra Lúcia Dantas de Moraes; Cleidiel Aparecido Araujo Lemos; Tatiana Prosini da Fonte; João Pedro Justino de Oliveira Limirio; Eduardo Piza Pellizzer (Elsevier, 2021)
Objective: This systematic review aims to assess the efficacy chlorhexidine chip as an adjunctive therapy of scaling and root planning on periodontal disease treatment. Material and methods: This study follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PRISMA) and was registered in the PROSPERO database (CRD42019148221). The search was performed in PubMed/MEDLINE, Scopus, and Cochrane databases until April 2020. The PICO question was: "Is the chlorhexidine chip (CHX) effective as an adjunctive therapy of scaling and root planning on periodontal disease treatment?". Inclusion criteria involved: randomized controlled clinical trials, with a minimum of 15 patients included on the sample and each patient has two sites of probing depth of ≥5 mm; The minimum follow up was at least 1 months of follow-up and the outcomes present in the studies probing depth (PD), plaque index (PI) and clinical attachment level (CAL) after scaling and root planning (SRP). Results: After searching the databases, 13 articles were selected for qualitative and 8 for quantitative analysis. Were included 427 patients, with a mean age of 45.6 years. The results shown that the association of chlorhexidine chips to scaling and root planning reduce periodontal pocket depths (P < 0.00001; MD −0.77 [CI −1.0 to −0.55]; I2 = 23%, P = 0.24), gain on the clinical attachment level (P < 0.0001; MD −0.57 [CI −0.86 to −0.27]; I2 = 33%, P = 0.18P < 0.0001) and reduction on plaque index (P = 0.04; MD −0.23 [CI −0.45 to −0.01]; I2 = 91%, P < 0.00001). Conclusions: Thus, we can conclude that chlorhexidine chip when used associated to scaling and root planning promoted a significant improvement the reduction of periodontal diseases.